Coaches' knowledge of injury and associated risk factors among young track and field athletes: A case study on the Western Cape Talent Development Programme (TDP) branch of the Mass participation, Opportunity and accessibility, Development and growth (MOD) programme for U12-U14 track and field athletes - Isaacs, Neda (Department of Health and Rehabilitation Sciences, 2022)
Background: The management, prevention, and recognition of injuries forms an integral part of coaches training. It is imperative that coaches are equipped with a sound understanding of specialised coaching to teach developing athletes correct performance techniques, promote strategies to reduce the risk of injury, and be able to determine the need for medical attention in the event of an injury (9). The South African Department of Cultural Affairs and Sport (DCAS) has created opportunities for young people living in low socio-economic settings to participate in various sports within the Mass participation, Opportunity and Development and growth (MOD) programme (10). Athletes showing potential for competing at a provincial or national level are selected into the specialised Talent Development Programmes (TDP). The MOD and TDP also provides an employment opportunity for coaches. At present, very little is known about the knowledge and practices of coaches working with young athletes in low socio-economic settings within South Africa. Aim and Objectives: The aim of the present study was to investigate the knowledge and practices of youth athletics coaches employed by the Western Cape (WC) TDP branch of the MOD within the under 12–14 year age group. The specific objectives were to: 1) describe the coaches qualifications and experience, using an online Demographic and Coaching Practices (D&CP) questionnaire; 2) assess coaches' knowledge regarding athlete development, injuries, and the management of injuries using an online Multiple Choice Quiz (MCQ); 3) describe coaches practices regarding injury prevention techniques using the D&CP questionnaire and 4) assess the relationship between the coaches a) experience and their MCQ scores, b) qualification and MCQ score, and c) qualification in first aid and the MCQ subsection score relating to injury and injury management. Method: A descriptive cross-sectional design was used. Inclusion criteria were: 1) coaches associated with the TDP for Athletics in the WC, 2) coaches with > one year's experience coaching U12-14 athletics, and 3) access to internet. Exclusion criteria were: 1) coaches < one season coaching experience. Ethics approval was granted by the University of Cape Town Human Research Ethics Committee (HREC REF 554/2019). The online MCQ consisted of 40 questions covering topics relating to coaches' knowledge and understanding of methods used to reduce the risk of injury and management of acute injuries. The D&CP questionnaire included questions related to the practices used by coaches to reduce injury risk and management protocols used during pre-season, training, or in competition. Results: Twenty-six coaches consented to participate; five coaches exercised their right to withdraw after having only completed the online MCQ component. Profile of coaches: 16 of the 21 coaches (76.19%) reported having a coaching qualification. Most coaches were certified by Athletics South Africa (n = 12; 57.14%). Most coaches (n = 17; 81%) held a first aid qualifications ranging from level one to three. Participants' experience ranged from less than five years to 15 years (median = 7 years; IQR = 10.5 years). Performance on the MCQ: The median score achieved by the coaches (n = 26) for the MCQ was 14 out of 40 points (35%; IQR = 4) and only two coaches achieved a score greater than 50%. Coaching Practices: Most coaches (71%) used 30-minute warm-up sessions which included various exercise techniques. During warm-ups, a few of the coaches (n = 11) included static stretching, while the majority (n = 19) included dynamic stretching techniques. During competition season, most coaches encouraged athletes to complete a cool-down following each event (n = 17; 80.95%). Most coaches (90%) incorporated a pre-season conditioning programme, lasting an average of 7.5 weeks (range = 2-16 weeks). Injury Management: 19% of coaches relied on the first aider present at each training session. Sixteen of the 21 coaches depended on medical professionals to make the final decision regarding to returning the athlete to training and competing, and 38.5% (n = 26) of coaches believed it was the coach or parents' decision. Relationship between MCQ Performance and Coaching profile: A moderate correlation between coaches' years of experience and MCQ score was found, however this was not significant (r = 0.43; p = 0.054), and weak non-significant correlations were found between MCQ scores were not significantly for groups of coaches who held or did not possesses a coaching qualification (u = 37; z = 0.21; p = 0.84). There was no difference between coaches who had a first aid qualification and those who did not on the MCQ test scores (u = 22; z = 1.03; p = 0.32). Discussion and Conclusion: Coaches' knowledge regarding injuries, practices used to reduce the risk of injuries, and the acute medical management of injuries is less than optimal. Several coaches performed poorly on the MCQ, and some practices used by the coaches in our sample were questionable. Despite the majority having qualifications in both coaching and first aid, their understanding relating to injuries and the practices used did not always reflect the latest guidelines for coaching youth athletes. The findings of the present study are similar to the findings of others studies (11). This may be as a result of insufficient coaching development throughout their careers. The present findings indicated that 42.3% of TDP coaches still use outdated warm-up techniques (i.e., static stretches). Coaches are generally aware of the importance of strength and conditioning programmes. The moderate correlation between years of experience and MCQ score suggests that coaches do gain implicit knowledge through their experience. As health professionals working in the field of sport, physiotherapists are key allies for sharing knowledge with coaches. Empowering coaches with the knowledge and skills required to reduce the risk of injury development and manage injuries appropriately may, in turn, provide developing athletes with the support they require.